1997
DOI: 10.1080/15216549700201231
|View full text |Cite
|
Sign up to set email alerts
|

Effect on product specificity of cyclodextrin glycosyltransferase by site‐directed mutagenesis

Abstract: Cyclodextrin glycosyltransferase (CGTase; EC 2.4.1.19) catalyzes the degradation of starch into cyclodextrins through an intrarnolecular transglycosylation reaction. Tyr‐89, Asn‐94, and Tyr‐100 are located near the putative active center. To analyze their roles in product specificity, Tyr‐89, Asn‐94, and Tyr‐100 of CGTase from alkalophilic Bacillus sp. 1‐5 were replaced with different amino acids. Among the mutants, the N94S mutant protein produced about two times more α‐cyclodextrin than the wild‐type at all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 3 publications
1
23
0
Order By: Relevance
“…Nevertheless, the mutants A and D retained a small cyclodextrin forming activity, whereas the G2-amylase has no cyclization activity, suggesting that the conformation of the five-residue insertion is different in Tabium CGTase mutants A and D. However, other differences between the two (mutant) enzymes may also contribute to this different reaction specificity. A simulation of the cyclization reaction catalyzed by B. circulans strain 251 CGTase has revealed that nearly all substrate binding subsites of CGTase contribute to the cyclization reaction , which is in agreement with mutation studies (van der Veen et al, 2000b;Leemhuis et al, 2002c;Parsiegla et al, 1998;Kim et al, 1997;Nakamura et al, 1993Nakamura et al, , 1994a. Thus, the limited cyclization activity of the five-residue insertion mutants might be explained by the functionality of the acceptor binding subsites of CGTase, which are still specialized to form cyclodextrins, even though the interactions at the remote donor subsites are not possible in these mutants.…”
Section: Increased Ratio Of Hydrolysis/cyclization Reaction Specificisupporting
confidence: 59%
“…Nevertheless, the mutants A and D retained a small cyclodextrin forming activity, whereas the G2-amylase has no cyclization activity, suggesting that the conformation of the five-residue insertion is different in Tabium CGTase mutants A and D. However, other differences between the two (mutant) enzymes may also contribute to this different reaction specificity. A simulation of the cyclization reaction catalyzed by B. circulans strain 251 CGTase has revealed that nearly all substrate binding subsites of CGTase contribute to the cyclization reaction , which is in agreement with mutation studies (van der Veen et al, 2000b;Leemhuis et al, 2002c;Parsiegla et al, 1998;Kim et al, 1997;Nakamura et al, 1993Nakamura et al, , 1994a. Thus, the limited cyclization activity of the five-residue insertion mutants might be explained by the functionality of the acceptor binding subsites of CGTase, which are still specialized to form cyclodextrins, even though the interactions at the remote donor subsites are not possible in these mutants.…”
Section: Increased Ratio Of Hydrolysis/cyclization Reaction Specificisupporting
confidence: 59%
“…Subsite Ϫ3 mutations in the alkalophilic Bacillus sp. I-5 CGTase also changed the product specificity [68].…”
Section: Protein Engineering Of the Product Specificity Of Cgtasementioning
confidence: 99%
“…This observation was in agreement with Y100F substitution in Bacillus sp. I-5 CGTase (93 in BA2-5a) did not change its K m (Kim et al, 1997) . Using the molecular docking approach, there was no interaction type change of Phe93 with substrate observed in Y93F CGTase compared to Tyr93 in wild type.…”
Section: Kinetic Parameters Of Y93fmentioning
confidence: 99%
“…The values of K m and k cat were determined by the nonlinear least-squares method with Hill-equation (Kim et al, 1997).…”
Section: Assay Of Protein Thermal Shiftmentioning
confidence: 99%
See 1 more Smart Citation